KEKERASAN MATERIAL BAJA KARBON RENDAH DENGAN METODE ROCKWELL - Junaidi Junaidi; Din Aswan Ritonga (Universitas Harapan Medan, 2019)
The development of technology is now so fast over time to help facilitate activities. The world of machinery has a very important role in the development of technology that exists today, on the one hand as a producer of new existing technology and the other hand as a consumer who needs technology in the production process.This research continues to be carried out to produce new technology with the aim of improving human welfare and making it easier for humans to do something. One way to determine the strength or toughness of a material and as a support for the specifications of a material is to use an impact test. Heat Treatment is one of the processes that play a role in the Manufacturing Industry with the aim of Mantenance Process and Production Process.Therefore in this study will be carried out a hardness test analysis of Low Carbon steel material with the Rockwell Method.